2021
DOI: 10.46636/recital.v3i1.148
|View full text |Cite
|
Sign up to set email alerts
|

Teores nutricionais de macronutrientes nas hastes, rizoma e raízes de gengibre ornamental sob deficiências de macronutrientes e boro

Abstract: O objetivo deste estudo foi avaliar os teores e acúmulos de macronutrientes em gengibre ornamental sob deficiências nutricionais de macronutrientes e boro. O experimento foi realizado na casa de vegetação do Departamento Ciência do Solo, na Universidade Federal de Lavras (MG). As plantas foram propagadas via sementes e germinadas em bandeja com 72 células individualizadas, usando vermiculita. Trinta dias após a germinação, as mudas foram transferidas para solução nutritiva completa. Após 60 dias de adaptação, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The greater accumulation of S in arrowroot propagated by whole rhizome can be attributed to the cumulative effect of the biofertilizer, which provided more S and, as the rhizome had higher amounts of this element, the plants were able to redistribute S to their leaves, resulting in higher leaf contents (Figure 2 C). Thus, as observed in the results of S presented here, Souza et al (2021) evaluated the contents of macronutrients in the stems and rhizome of ornamental ginger (Zingiber spectabile Griff.) subjected to nutrient solutions and observed that S contents in the rhizome were higher than those in the stems.…”
Section: /9mentioning
confidence: 85%
“…The greater accumulation of S in arrowroot propagated by whole rhizome can be attributed to the cumulative effect of the biofertilizer, which provided more S and, as the rhizome had higher amounts of this element, the plants were able to redistribute S to their leaves, resulting in higher leaf contents (Figure 2 C). Thus, as observed in the results of S presented here, Souza et al (2021) evaluated the contents of macronutrients in the stems and rhizome of ornamental ginger (Zingiber spectabile Griff.) subjected to nutrient solutions and observed that S contents in the rhizome were higher than those in the stems.…”
Section: /9mentioning
confidence: 85%